Development of STEM -Based Learning Media using Android Platform to Improve Students' Problem Solving Abilities - Wulanningtyas, Melania Eva; Arfi, Arfi; Ramadhan, Ardhika Fajar (Jurnal Pendidikan MIPA, 2023)
Abstract: This research aims to develop Android-based learning media using a STEM approach to enhance students' problem-solving abilities. The learning media was developed using the 4D model and tested on 192 eighth-grade students from six junior high schools in Yogyakarta. The research results indicate that the developed learning media fulfills aspects of validity, practicality, and effectiveness. Validity was confirmed through assessments by subject matter experts and media experts, scoring 82 and 73.5, respectively, falling into the categories of very good and good. Practicality was established through small-scale and large-scale tests, scoring 80.27 and 76.34, respectively, categorized as good in both instances. Effectiveness was determined through effectiveness tests, including one-sample t-test and mean different test. The one-sample t-test results indicated an improvement in students' problem-solving abilities with an average increase of 21.2769 in the control class and 42.5423 in the experimental class. The conclusion drawn from this research is that Android-based learning media using a STEM approach is effective in enhancing students' problem-solving abilities. Keywords: learning media, STEM, mobile application. Abstrak: Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis android dengan pendekatan STEM untuk meningkatkan kemampuan pemecahan masalah siswa. Media pembelajaran dikembangkan dengan model 4D untuk diuji coba kepada 192 siswa kelas 8 dari 6 SMP di Yogyakarta. Hasil dari penelitian menunjukkan bahwa media pembelajaran yang dibuat memenuhi aspek valid, praktis, dan efektif. Aspek valid diperoleh melalui penilaian ahli materi dan ahli media dengan nilai 82 dan 73,5 serta masuk pada kategori sangat baik dan baik. Aspek praktis diperoleh melalui uji skala kecil dan uji skala besar dengan nilai 80,27 dan 76,34 serta masuk kategori baik dan baik. Aspek efektif diperoleh melalui uji efektivitas yang meliputi one sample t-test dan mean different test. Berdasarkan one sample t-test diperoleh hasil bahwa terdapat peningkatan kemampuan pemecahan masalah siswa dengan peningkatan rata-rata sebesar 21,2769 pada kelas control dan 42,5423 pada kelas eksperimen. Kesimpulan dari penelitian ini adalah media pembelajaran berbasis android dengan pendekatan STEM efektif untuk meningkatkan kemampuan pemecahan masalah siswa.  Kata kunci: android, media pembelajaran, STEM, 4D. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp890-900